2006
DOI: 10.1128/jb.00371-06
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Five Rickettsia prowazekii Proteins Annotated as ATP/ADP Translocases (Tlc): Only Tlc1 Transports ATP/ADP, While Tlc4 and Tlc5 Transport Other Ribonucleotides

Abstract: The obligate intracytoplasmic pathogen Rickettsia prowazekii relies on the transport of many essential compounds from the cytoplasm of the eukaryotic host cell in lieu of de novo synthesis, an evolutionary outcome undoubtedly linked to obligatory growth in this metabolite-replete niche. The paradigm for the study of rickettsial transport systems is the ATP/ADP translocase Tlc1, which exchanges bacterial ADP for host cell ATP as a source of energy, rather than as a source of adenylate. Interestingly, the R. pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 55 publications
1
60
0
1
Order By: Relevance
“…This is consistent with secondarystructure predictions of biochemically characterized nucleotide transport proteins, for which between 11 and 12 transmembrane domains are recognized (7,26,43,63,67,75). The only nucleotide transporter whose topology has been investigated experimentally in some detail is the ATP/ADP translocase from Rickettsia prowazekii, showing 12 transmembrane domains (1,2,6).…”
Section: Four Putative Nucleotide Transport Proteins In S Negevensissupporting
confidence: 69%
See 3 more Smart Citations
“…This is consistent with secondarystructure predictions of biochemically characterized nucleotide transport proteins, for which between 11 and 12 transmembrane domains are recognized (7,26,43,63,67,75). The only nucleotide transporter whose topology has been investigated experimentally in some detail is the ATP/ADP translocase from Rickettsia prowazekii, showing 12 transmembrane domains (1,2,6).…”
Section: Four Putative Nucleotide Transport Proteins In S Negevensissupporting
confidence: 69%
“…Another possible explanation for why no substrate could be identified for SnNTT4 could be that, unlike other nucleotide transporters characterized in E. coli, SnNTT4 requires posttranslational modifications that the heterologous host cannot perform. It should be noted that two of the five putative nucleotide transporters from R. prowazekii also failed to take up any of the nucleoside mono-, di-, and triphosphates tested, although the presence of mRNA of those transporters suggested that they are required during intracellular growth (7).…”
Section: Vol 193 2011mentioning
confidence: 99%
See 2 more Smart Citations
“…NTTs may be divided into three different classes, nucleotide antiporters (class I), proton-driven nucleotide symporters (class II), and NAD/ADP antiporters (class III) (7). NTTs appear to be restricted to a limited number of obligate intracellular bacteria other than the members of the order Chlamydiales, including members of the order Rickettsiales, Lawsonia spp., and "Candidatus Liberbacter spp.," as well as plastids, which all possess ATP/ADP translocases (class I NTTs), presumably to acquire energy from their host (8)(9)(10)(11)(12). To date, class II and III NTTs have been characterized only in Chlamydia trachomatis and P. amoebophila (7,10,13).…”
mentioning
confidence: 99%